2005
DOI: 10.1109/tnet.2005.845549
|View full text |Cite
|
Sign up to set email alerts
|

Achieving near-optimal traffic engineering solutions for current OSPF/IS-IS networks

Abstract: Traffic engineering is aimed at distributing traffic so as to "optimize" a given performance criterion. The ability to carry out such an optimal distribution depends on both the routing protocol and the forwarding mechanisms in use in the network. In IP networks running the OSPF or IS-IS protocols, routing is over shortest paths, and forwarding mechanisms are constrained to distributing traffic uniformly over equal cost shortest paths. These constraints often make achieving an optimal distribution of traffic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(139 citation statements)
references
References 11 publications
2
136
0
1
Order By: Relevance
“…Some variations of this TE algorithm were also designed to obtain a set of link weights that is robust to traffic demand uncertainty [11] and link failures [12]. Sridharan et al [3] revealed that near-optimal TE solutions can be achieved by carefully assigning traffic to some selected next-hops over ECMP paths at each eligible router. By modifying the next-hop entry in the forwarding table of a limited number of routers, uneven traffic splitting based on individual routing prefixes can be emulated.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Some variations of this TE algorithm were also designed to obtain a set of link weights that is robust to traffic demand uncertainty [11] and link failures [12]. Sridharan et al [3] revealed that near-optimal TE solutions can be achieved by carefully assigning traffic to some selected next-hops over ECMP paths at each eligible router. By modifying the next-hop entry in the forwarding table of a limited number of routers, uneven traffic splitting based on individual routing prefixes can be emulated.…”
Section: Related Workmentioning
confidence: 99%
“…Once the optimized MT-IGP link weights have been configured in the network, dynamic traffic control through traffic splitting at source nodes can be performed through the provisioned diverse IGP paths. Arbitrary traffic splitting is usually required for achieving optimal TE performance [2,3,5]. However, in plain OSPF/IS-IS networks, this prerequisite is not possible since these protocols only allow equal traffic splitting onto multiple equal cost paths.…”
Section: Ample Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to tackle this difficulty, either the single path routing assumption or a couple of alternative strategies like the management of next hop selection or edge-based traffic engineering have been used. We cite Bley and Koch (2002), Lin and Wang (1993), and Tomaszewski et al (2005) as examples for unsplit routing while we refer to Parmar et al (2009), Sridharan et al (2003), and Wang et al (2005) for the latter case. Broström and Holmberg (2005), De Giovanni et al (2005), Parmar et al (2009), Pióro et al (2002), and Tomaszewski et al (2005) also show mixed-integer modeling examples for incorporating the ECMP rule.…”
Section: Introductionmentioning
confidence: 97%